FBXL10 regulates cardiac dysfunction in diabetic cardiomyopathy via the PKC β2 pathway. Issue 4 (31st January 2019) - Yin, Leilei; Fang, Yingying; Song, Tao; Lv, Dan; Wang, Zheng; Zhu, Li; Zhao, Zihui; Yin, Xinhua
Abstract: Diabetic cardiomyopathy (DCM) is a condition associated with significant structural changes including cardiac tissue necrosis, localized fibrosis, and cardiomyocyte hypertrophy. This study sought to assess whether and how FBXL10 can attenuate DCM using a rat streptozotocin (STZ)‐induced DCM model system. In the current study, we found that FBXL10 expression was significantly decreased in diabetic rat hearts. FBXL10 protected cells from high glucose (HG)‐induced inflammation, oxidative stress, and apoptosis in vitro. In addition, FBXL10 significantly activated PKC β2 signaling pathway in H9c2 cells and rat model. The cardiomyocyte‐specific overexpression of FBXL10 at 12 weeks after the initial STZ administration attenuated oxidative stress and inflammation, thereby reducing cardiomyocyte death and preserving cardiac function in these animals. Moreover, FBXL10 protected against DCM via activation of the PKC β2 pathway. In conclusion, FBXL has the therapeutic potential for the treatment of DCM.